The Role of Organizational Culture and Empowerment in Enhancing Teacher Commitment: Work Motivation as a Mediator - Maulana, Adam; Wulandari, Dian; Hidayat, Rais (Managere: Indonesian Journal of Educational Management, 2026)
This study is motivated by the need for vocational high school teachers to continuously improve their competencies, uphold professional ethics, and foster effective learning so that graduates are ready to work, become entrepreneurs, or continue their education. However, the professional commitment of private vocational high school teachers in Ciampea District remains suboptimal. The study aims to examine the influence of organizational culture, empowerment, and work motivation on professional commitment, with work motivation as an intervening variable. The subjects were permanent teachers at vocational high schools in Ciampea District, Bogor, with a total of 200 and 134 respondents, respectively. Data were collected via validated and reliable questionnaires and analyzed using path analysis and SITOREM. Results show significant direct effects of organizational culture (β=0.621), empowerment (β=0.221), and work motivation (β=0.148) on professional commitment; organizational culture (β=0.535) and empowerment (β=0.169) on work motivation; and work motivation mediates the influence of organizational culture (β=0.261) and empowerment (β=0.321) on professional commitment. The study implies that increasing teacher commitment should prioritize indicators such as sense of loss, willingness to invest, values, independence, appreciation, and rewards, supporting the development of professional, adaptive, and work-ready vocational school graduates.